Hepatitis C and HIV-1 coinfection. Issue 4 (1st October 2002) - Mohsen, A H; Easterbrook, P; Taylor, C B; Norris, S
Abstract : Hepatitis C virus (HCV) has emerged as the cause of the second major epidemic of viral infection after human immunodeficiency virus (HIV) within the past two decades, and coinfection of HIV and HCV represents a growing problem for the future. This article reviews the current evidence on the epidemiology and clinical implications of an interaction between HIV-1 and HCV infection, and the current status of the management of patients with combined infection.